SPHYNCS: The Use of the Swiss Narcolepsy Scale in a New Cohort of Patients with Narcolepsy and Its Borderland and Review of the Literature - Kseniia Zub; Jan D. Warncke; Julia van der Meer; Elena S. Wenz; Livia G. Fregolente; Panagiotis Bargiotas; Gülçin Benbir Şenel; Christian Sturzenegger; Gert Jan Lammers; Ulf Kallweit; Markus H. Schmidt; Ramin Khatami; et al. (Clinical and Translational Neuroscience, 2023)
Introduction and aims: Narcolepsy type 1 (NT1) is a central disorder of hypersomnolence (CDH) characterized by excessive daytime sleepiness and cataplexy. The Swiss Narcolepsy Scale (SNS), which includes the updated and short (sSNS) versions, has recently been introduced as a reliable diagnostic tool for identifying NT1. This study aims to assess the validity of the SNS scales in a new cohort of patients with CDH, while also introducing the French and Italian versions of the SNS and providing a summary of the existing literature on SNS. Materials and methods: The current study is based on the international Swiss Primary Hypersomnolence and Narcolepsy Cohort Study (iSPHYNCS) which aims to identify new biomarkers for CDH. Diagnostic accuracy of the SNS was assessed by calculating sensitivity, specificity, positive predictive value, and negative predictive value. Results: In our population, 108 participants with suspected CDH (including 28 NT1 patients) and 14 healthy controls completed the scale. Original SNS, updated SNS and sSNS scores showed a high sensitivity (86%, 89% and 79%, respectively) and high specificity (96%, 90% and 95%, respectively) for diagnosing NT1 compared to other CDH. The French version was completed by 5 participants, and the Italian version by 8 participants. Regarding previous studies, the SNS has now been assessed in six different populations, involving a total of 1247 subjects (including 326 with narcolepsy with cataplexy/NT1), suggesting high sensitivity (85–100%) and specificity (86–100%) of the SNS for the diagnosis of NT1. Conclusion: The SNS is a simple screening tool validated in seven languages (German, English, French, Italian, Dutch, Turkish and Japanese), demonstrating high sensitivity and specificity for the diagnosis of NT1.